“Do it for the gram” : the effect of Instagram on body image, self-esteem, and social comparison, among students at Reykjavík University - Emma Rúnarsdóttir 1997- (2020)
Social media use has grown in recent years and has become a significant part of people's social lives. Instagram is one of the most popular social media sites, with 163.900 active users on Instagram in Iceland. The main purpose of the study was to examine the impact of Instagram on factors such as body image, self-esteem, and social comparison on RU students. Correspondingly, to determine if there was any difference by the impact of Instagram for adults and adolescents. An email was sent to all students at Reykjavik University on the 24th of April 2020. 90 participants in total took part in this study, 28 males (30.8%), and 62 females (68.1%). The age range was from 20-53 (M= 26.9). The results revealed that: (1) There was not a significant difference in participants' body image, self-esteem, and social comparison for those who had an Instagram account, and for those who did not have an Instagram account. (2) There was a positive correlation between self-esteem and time spent on Instagram. (3) There was not a correlation for 'likes' received on Instagram, nor posting on Instagram on body image, social comparison, and self-esteem. (4) There was a positive correlation between body image and cosmetic surgery. (5) time spent on Instagram, posting to Instagram, the frequency of photo editing, ‘likes’, and age of the participant, could not predict social comparison, body image, nor self-esteem. (6) 51.8% of participants have experienced pressure related to Instagram. Key words: Instagram, social media, self-esteem, body image, social comparison Notkun samfélagsmiðla hefur mikið aukist á undanförnum árum, og er orðinn mikilvægur hlutur af lífi fólks. Instagram er einn vinsælasti samfélagsmiðill í heiminum, með 163.900 notendur á Íslandi. Rannsókn þessi skoðaði áhrif Instagram á líkamsímynd, sjálfstraust, og félagslegan samanburð nemenda við Háskólann í Reykjavík. Einnig hvort það væri munur á áhrifum Instagram hjá unglingum og fullorðnum. Tölvupóstur var sendur á alla nemendur við Háskólann í Reykjavík þann 24 apríl ...